Employer branding constrains applicants' job seeking behaviour? - Gomes, D.; Neves, J. (Journal of Work and Organizational Psychology, 2010)
Researchers have been consistent in advising managers to invest on the organization’s employer brand, based on the argument that it will benefit recruitment practice. However, this premise has been majorly sustained following an organizational point of view. As such, the employer branding effects on applicants’ job search behavior of applying to a vacancy remains undetermined. Main purpose of this study is to understand if employer branding constrains applicants’ job seeking behavior. We propose that applicants develop the desire of submitting to a vacancy through a process having the organizational attributes as its predictor and attractiveness as its mediator. We then investigate if and how employer branding constrains this process, by evaluating its moderating effect. Using confirmatory analysis methodology, we found that employer branding moderates the proposed job seeking process. A positive employer branding has strengthened the process leading to the intention to apply to a vacancy, when compared with neutral or negative employer brandings. This explains applicants’ desire of submitting to a vacancy. Based on our results, we suggest directions for practitioners concerning recruitment efficacy.